Rancang Bangun Mesin Kompresor Angin 90 Watt Berbasis Panel Surya Monocrystalline 120 WP - Erfan Ali Mubarok; Basuki Basuki; Mohammad Munib Rosadi; Dian Anisa Rokhmah Wati (JOURNAL SAINS STUDENT RESEARCH, 2024)
At this time the dry season tends to be longer than it should be, this can be utilized as alternative energy which can be used as a substitute for fossil fuels, alternative energy that can be utilized during the hot dry season as a substitute for fossil energy is solar power generation (PLTS) which can be used for various needs, one of which is used for wind compressors, air compressors usually suck air from the atmosphere, but there are also those that attract air or gas with a pressure higher than atmospheric pressure. A 90 watt air compressor based on 120 WP monocrystalline solar cells is one of the applications for solar power generation (PLTS), This 90 watt wind compressor based on 120 WP monocrystalline solar cells uses the R&D (Research And Development) method. This design process begins with making a tool design including frame design, solar panels, ESP 32, battery, 90 watt air compressor, inverter, The results of the design of a 90 watt wind compressor based on a 120 Wp monocrystalline solar panel. This tool has frame dimensions of 800 x 720 x 500 mm using hollow iron (25 x 25 mm), this tool uses a battery type VOZ VD12-12 (12V 7.0AH), SCC (Solar Charge Control) with type STEC ZS10-10A, ESP 32 as the controller, uses an inverter which functions to change the current from DC to AC with a voltage of 2000 W, and uses a 90 watt air compressor.